STUDI DESKRIPTIF KEGIATAN PENGEMBANGAN DIRI BERNYANYI PADA ANAK TUNANETRA DI SEKOLAH LUAR BIASA WACANA ASIH KOTA PADANG - Zaina Riansyah; Jagar Lumbantoruan; Harisnal Hadi (SENDRATASIK UNP, 2018)
AbstractThis study was based on research finding that there were blind children who were talented in singing at SLB Wacana Asih Padang. Therefore, this study was done for the purpose of self-development activities of singing on blind children in SLB Wacana Asih Padang in order to expressed a description of actualizing, phenomenon background, social reality, and perceptions of research target. This study was classified as qualitative research which used descriptive approach. Instruments in this study were the researchers  Techniques of data collection were done by using observation, interview, documentation and libarary research. Result of this research showed that students could develop and express themeselves in distributing their interest and talent. In the purpose of its implementation psychologically, they were directed to have the confidence and bravery to speak and move, and have the feeling that they wereaqualwith the normal children. In the implementation ofself- development of singing, teachers should apply the method of imitation i.e. the way of presentation of lessons where teachers gave, so the students could practice and recite the words of the song lyric continuously. Keywords: Self-Development; Blind Children.